2007
DOI: 10.1196/annals.1423.071
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Reactivity in the Dimeric Intravenous Immunoglobulin Fraction

Abstract: Therapeutic intravenous immunoglobulin (IVIg) preparations contain antibodies reflecting the cumulative antigen experience of the donor population. IVIg contains variable amounts of monomeric and dimeric IgG, but there is little information available on their comparative antibody specificities. We have isolated highly purified fractions of monomeric and dimeric IgG by size-exclusion chromatography. Following treatment of all fractions at pH4, analyses by immunodot and immunocytology on human cell lines showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
(83 reference statements)
0
13
1
Order By: Relevance
“…We isolated IVIg-protein complexes formed in living cells which permitted to reveal the genuine interaction of IVIg with native cellular proteins. This is in contrast to another study by Schaub et al in which the autoreactivity of IVIg with various cellular proteins was determined using denatured proteins from cell lysates [25]. Interestingly, some of the proteins identified by Schaub et al as targets of IVIg were also identified in the present study (eg.…”
Section: Discussioncontrasting
confidence: 72%
“…We isolated IVIg-protein complexes formed in living cells which permitted to reveal the genuine interaction of IVIg with native cellular proteins. This is in contrast to another study by Schaub et al in which the autoreactivity of IVIg with various cellular proteins was determined using denatured proteins from cell lysates [25]. Interestingly, some of the proteins identified by Schaub et al as targets of IVIg were also identified in the present study (eg.…”
Section: Discussioncontrasting
confidence: 72%
“…Nevertheless, IVIG does not just represent the sum of IgG NAbs and Abs from these donors; it is enriched in IgG dimers, and multimers (which can have adverse effects) are largely eliminated. The dimeric fraction consists primarily of idiotype-anti-idiotypic pairs [75] that presumably form more efficiently between antibodies from distant donors than with autologous ones in purified IgG and plasma of individuals. IVIG originally was developed to treat primary immune deficiencies.…”
Section: Box 2 Intravenous Immunoglobulin (Ivig)mentioning
confidence: 99%
“…NAbs recognize evolutionarily conserved molecules with an affinity for self antigen that ranges from 10 À5 to 10 À8 M. Many NAbs are polyreactive [7], which does not mean non-specific [74]. NAbs are interconnected and are complexed with anti-idiotypic IgM and IgG NAbs [75]. By virtue of their capacity to recognize a wide range of antigens, NAbs provide the first line of defense against microbial infections.…”
Section: Introductionmentioning
confidence: 99%
“…36,77 On the one hand the challenge for the fractionating industry is to limit dimer/oligomer formation over the shelf-life of a product without removal of IgG molecules potentially able to form dimers because the IgG molecules able to form dimers might harbor a particular fraction of IgG, including NAbs, and Id/anti-Id dimers might be of advantage for the treatment of autoimmune and inflammatory diseases. Recently it emerged that the fraction of dimers in IVIG apparently have enriched some properties usually considered being of benefit for patients affected by autoimmune and inflammatory diseases [78][79][80] or for patients needing first-line defense because of infection. 80a Thus, after the crude fractionation and the polishing steps appropriate stabilizers have to be added in order not to reduce the content in IgG molecules having the potential to form dimers, while keeping effective complex formation low.…”
Section: Nabs and Dimers In Ivigmentioning
confidence: 99%